2014
DOI: 10.1007/s12013-014-0365-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Diabetic Neuropathy: Generation of Free Radical Species in the Glycation Reaction and Gene Polymorphisms Encoding Antioxidant Enzymes to Genetic Susceptibility to Diabetic Neuropathy in Population of Type I Diabetic Patients

Abstract: Diabetic neuropathy (DN) represents the main cause of morbidity and mortality among diabetic patients. Clinical data support the conclusion that the severity of DN is related to the frequency and duration of hyperglycemic periods. The presented experimental and clinical evidences propose that changes in cellular function resulting in oxidative stress act as a leading factor in the development and progression of DN. Hyperglycemia- and dyslipidemia-driven oxidative stress is a major contributor, enhanced by adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 103 publications
0
64
0
4
Order By: Relevance
“…Chronic hyperglycaemia is widely accepted as a trigger of excessive production of reactive oxygen species (ROS) in all cells, as is the fact that this toxic process is exacerbated by a concomitant reduction in endogenous antioxidant defences 61 . For example, genetic variations and poly morphisms in endogenous antioxidant enzymes have been associated with an increased susceptibility to diabetic neuropathy 62 . Potential sources of ROS in peripheral nerves include the polyol pathway, the mitochondrial electron transport chain, RAGE (receptor for advanced glycosylation end products) signalling, and NADPH oxidases and nitric oxide synthases [63][64][65] .…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Chronic hyperglycaemia is widely accepted as a trigger of excessive production of reactive oxygen species (ROS) in all cells, as is the fact that this toxic process is exacerbated by a concomitant reduction in endogenous antioxidant defences 61 . For example, genetic variations and poly morphisms in endogenous antioxidant enzymes have been associated with an increased susceptibility to diabetic neuropathy 62 . Potential sources of ROS in peripheral nerves include the polyol pathway, the mitochondrial electron transport chain, RAGE (receptor for advanced glycosylation end products) signalling, and NADPH oxidases and nitric oxide synthases [63][64][65] .…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Regarding the mechanism through which neuropathy develops, previously published papers showed that hyperglycemia generates free radicals, contributing to the development and progression of diabetes complications. There is large evidence that there is a relationship between the severity of diabetic neuropathy and the frequency and duration of hyperglycemic periods [8]. For this reason, improving oxidative stress may be a way to reduce diabetic complications [9,10], and this is probably the way α-lipoic acid acts.…”
Section: Introductionmentioning
confidence: 99%
“…These pathways includes Janus kinase/Signal transducer activator of transcription 3 pathway and extracellular signal-regulated kinases pathway; it also activates IKKa/nuclear factor-kappa B pathway, resulting in the suppression of apoptosis and cell proliferation in hepatocytes [32e34]. In this study, hepatic inflammation was not observed in the hyperglycemic STZ and Starch groups, although hyperglycemia reportedly induces inflammation in other tissues such as the microand macrovasculature through reactive oxygen species or advanced glycation end product level elevation or epigenetic changes [35]. Steatosis is the most common cause of hepatic inflammation [29].…”
Section: Discussionmentioning
confidence: 69%